2006
DOI: 10.1002/imhj.20082
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postnatal antecedents of a home‐visiting intervention and family developmental outcome

Abstract: This is a study of the pre- and postnatal antecedents of select indices of 6 to 24 months mother-child and child social-emotional development. The following hypotheses guided the study: 1. That a mother who is secure before the birth of her child will be more involved in the work of the home-visiting intervention, and will by child age 24 months be more responsive to the needs of her child, encourage the autonomy of her child, and use verbal and positive forms of control. In this relationship context, the 2 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…Our particular findings are both consistent and inconsistent with existing studies. Our findings are consistent with those studies that have found better program participation or outcomes for more secure mothers (Heinicke et al, 2006; Moran et al, 2005; Robinson et al, 2002; Spieker et al, 2005). Our findings are inconsistent with those that have found better program participation for mothers who are depressed and/or higher on attachment avoidance or anxiety (Duggan et al, 2009; Olds et al, 2008 [for mothers with fewer “psychological resources”]; Robinson & Emde, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our particular findings are both consistent and inconsistent with existing studies. Our findings are consistent with those studies that have found better program participation or outcomes for more secure mothers (Heinicke et al, 2006; Moran et al, 2005; Robinson et al, 2002; Spieker et al, 2005). Our findings are inconsistent with those that have found better program participation for mothers who are depressed and/or higher on attachment avoidance or anxiety (Duggan et al, 2009; Olds et al, 2008 [for mothers with fewer “psychological resources”]; Robinson & Emde, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…A lack of self-disclosure may limit the extent to which a mother communicates her or her child's needs, which may then limit the extent to which services providers can help to address these needs. Further support for the proposed weaker program effects for mothers higher on attachment avoidance or anxiety comes from three studies that used the AAI and found greater program engagement or impacts for secure mothers (Heinicke et al, 2006; Spieker, Nelson, DeKlyen, & Staerkel, 2005), or for mothers who were not classified with the AAI as unresolved (with respect to loss or trauma; Moran, Pederson, & Krupka, 2005). …”
mentioning
confidence: 99%
“…This time point is critical as extant research largely supports the adverse effects of maternal depressive symptoms on sensitive parenting and subsequent quality of attachments formed between mothers and children (Diener et al 2003; Goodman and Gotlib, 2002; Lyons-Ryth et al 2002; Mills-Koonce et al 2008). Furthermore, recent research supports the influence of maternal attachment style, and maternal depressive symptoms on the ability to benefit from early intervention programs aimed at improving parent-child interaction (Berlin et al 2011; Duggan et al 2009; Heinicke et al 2006). Mothers whose attachment styles make it difficult to connect with their unborn child may also have difficulty connecting with an interventionist charged with engaging the mother in a working alliance (Duggan et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Heinicke et al (2006), using the AAI with pregnant women, found that secure mothers in the treatment group had better parenting and child outcomes than did insecure mothers. However, another study found that maternal attachment, as measured by the AAI, did not moderate Early Head Start program impacts (Spieker et al 2005).…”
mentioning
confidence: 99%